Bone-Healing Pattern on the Surface of Titanium Implants at Cortical and Marrow Compartments in Two Topographic Sites: an Experimental Study in Rabbits - Soto-Peñaloza, David (Materials (Basel), 2018)
This study evaluates the bone-healing patterns on the surface of titanium implants at the cortical and marrow compartments of bicortically-installed implants in the diaphysis and metaphysis of rabbit tibiae. In 27 New Zealand rabbits, two implants, one for each macro-design and with equal resorbable blasted media (RBM) implant surfaces, were randomly implanted in the diaphysis or metaphysis of each tibia. The flaps were sutured to allow submerged healing. The animals were sacrificed after two, four, or eight weeks, with nine weeks used for the period of healing. Ground sections were prepared and analyzed. No statistically significant differences were found between the two groups for newly formed bone in contact with the implant surface after two, four, and eight weeks of healing. Bone apposition in the marrow compartment was slightly higher in the diaphysis compared to metaphysis regions across healing stages. Despite the limitations of the present study, it can be concluded that new bone apposition was better than average in the cortical compartment as compared to the marrow compartments. Bone morphometry and density may affect bone apposition onto the implant surface. The apposition rates were slightly better at both the cortical and marrow compartments in diaphysis as compared to metaphysis sites. The new bone formation at the marrow compartment showed slightly better increasing values at diaphysis compared to metaphysis implantation sites.